Acute transient corneal endothelial changes following selective laser trabeculoplasty. (25th June 2013) - White, Andrew JR; Mukherjee, Achyut; Hanspal, Inderraj; Sarkies, Nicholas J; Martin, Keith R; Shah, Peter
Abstract Background To report for the first time acute transient corneal endothelial changes following selective laser trabeculoplasty. Design Observational case series at a tertiary referral ophthalmological centre in the United Kingdom (Addenbrooke's Hospital, Cambridge) Participants Ten consecutive routinely treated patients. Methods Baseline measurements of corneal specular microscopy, endothelial cell counts and in vivo confocal microscopy were performed prior to routine selective laser trabeculoplasty treatment. Repeat measurements were made approximately 1 h later and at a 6‐week follow up. Main Outcome Measures Endothelial in vitro laser confocal microscopy, specular microscopic endothelial cell count, endothelial morphology, visual acuity and intraocular pressure. Results All patients had normal corneal endothelia prior to routine selective laser trabeculoplasty treatment, where 180 degrees of angle was treated. Approximately an hour afterwards, nearly all patients still had normal specular microscopy and cell counts (2237 ± 211 cells/mm2) but had subtle endothelial changes on slit‐lamp examination. These changes were found diffusely across the cornea. The changes were not present at the 6‐week follow up and cell counts remained unchanged (2278 ± 242 cells/mm2). Acuity remained unchanged throughout and the patients were not aware of these changes subjectively. Conclusions Selective laser trabeculoplasty appears to cause transient corneal endothelial changes in most patients that have no impact on cell count or visual acuity. Further work is required to elucidate the mechanism of this phenomenon and any long‐term impact.